2019
DOI: 10.1016/j.engstruct.2018.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-structural masonry brick infill walls on the robustness of a RC framed building severely damaged due to a landslide

Abstract: Western countries are increasingly demanding for robust structures, i.e., structures capable of withstanding local damage caused by unforeseen extreme events without triggering a progressive collapse, thus reducing the magnitude and proportion of the resulting consequences.In this paper, the robustness of framed RC buildings is analysed by comparing the reliability of the damaged structure with that of the original structure and considering (or not) the contribution of the masonry infill walls. To validate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Most of codes consider infills as a non-structural element. The study finds that the infills increases the robustness index of building which prevents the building from collapse by providing the alternative load path [5]. H. Chaulagain et al (2014) upon their parametric studies determined the lower value of inter-storey drift favoring the performance of building.…”
Section: Introductionmentioning
confidence: 94%
“…Most of codes consider infills as a non-structural element. The study finds that the infills increases the robustness index of building which prevents the building from collapse by providing the alternative load path [5]. H. Chaulagain et al (2014) upon their parametric studies determined the lower value of inter-storey drift favoring the performance of building.…”
Section: Introductionmentioning
confidence: 94%
“…It was concluded that the infill masonry wall can enhance vertical resistance of bare frame by around 280% on average and up to 500%. According to numerical studies [21][22][23], the use of masonry infill walls for multi-story building can considerably increase robustness. Furthermore, studies [24][25][26][27][28] proved that, even with openings, infill walls could greatly improve the performance of bare frames significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, low strength materials and empirical calculation methodologies were applied, which resulted in more robust structures. The construction techniques were improved with the use of more resistant materials alongside new alternatives methodologies (Barros et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The non-reinforced structural masonry of concrete blocks is composed of mortar-laid blocks, that may contain reinforcements for constructive or binding purposes. This type of masonry consists of structural elements that have various functions, but collectively provide structural stability (Rizzatti et al, 2012;Barros et al, 2019). This technique can rationalize all construction stages, optimizing time, materials and human resources (Juste, 2001).…”
Section: Introductionmentioning
confidence: 99%